A Biomimetic Polymer Magnetic Nanocarrier Polarizing Tumor‐Associated Macrophages for Potentiating Immunotherapy. Issue 38 (18th August 2020) - Liu, Lingqiao; Wang, Yi; Guo, Xing; Zhao, Jingya; Zhou, Shaobing
Abstract: The progress of antitumor immunotherapy is usually limited by tumor‐associated macrophages (TAMs) that account for the highest proportion of immunosuppressive cells in the tumor microenvironment, and the TAMs can also be reversed by modulating the M2‐like phenotype. Herein, a biomimetic polymer magnetic nanocarrier is developed with selectively targeting and polarizing TAMs for potentiating immunotherapy of breast cancer. This nanocarrier PLGA‐ION‐R837 @ M (PIR @ M) is achieved, first, by the fabrication of magnetic polymer nanoparticles (NPs) encapsulating Fe3 O4 NPs and Toll‐like receptor 7 (TLR7) agonist imiquimod (R837) and, second, by the coating of the lipopolysaccharide (LPS)‐ treated macrophage membranes on the surface of the NPs for targeting TAMs. The intracellular uptake of the PIR @ M can greatly polarize TAMs from M2 to antitumor M1 phenotype with the synergy of Fe3 O4 NPs and R837. The relevant mechanism of the polarization is deeply studied through analyzing the mRNA expression of the signaling pathways. Different from previous reports, the polarization is ascribed to the fact that Fe3 O4 NPs mainly activate the IRF5 signaling pathway via iron ions instead of the reactive oxygen species‐induced NF‐κB signaling pathway. The anticancer effect can be effectively enhanced through potentiating immunotherapy by the polarization of the TAMs in the combination of Fe3 O4 NPs and R837. Abstract : A biomimetic polymer magnetic nanocarrier is developed, which possesses a great capacity of potentiating immunotherapy of breast cancer through selectively targeting and polarizing tumor‐associated macrophages. The polarization is ascribed to the fact that Fe3 O4 nanoparticles mainly activate the IRF5 signaling pathway via iron ions instead of the previously reported reactive oxygen species‐induced NF‐κB signaling pathway.